Antigenotoxicity and antimutagenicity of ethanolic extracts of Brazilian green propolis and its main botanical source determined by the Allium cepa test system - Roberto, Matheus Mantuanelli [UNESP]; Jamal, Claudia Masrouah; Malaspina, Osmar [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Soc Brasil Genetica, 2016)
Brazilian green propolis is a resinous substance prepared by bees from parts of the plant Baccharis dracunculifolia. As it possess several biological properties, this work assessed the cytotoxic/anticytotoxic, genotoxic/antigenotoxic and mutagenic/antimutagenic potential of ethanolic extracts of Brazilian green propolis (EEGP) and of B. dracunculifolia (EEBD), by means of the Allium cepa test system. The effects were evaluated by assessing the chromosomal aberrations (CA) and micronuclei (MN) frequencies on meristematic and F1 generation cells from onion roots. Chemical analyses performed with the extracts showed differences in flavonoid quality and quantity. No genotoxic or mutagenic potential was detected, and both extracts were capable of inhibiting cellular damage caused by methyl methanesulfonate (MMS) treatment, reducing the frequencies of CA and MN. By these data, we can infer that, independent of their flavonoid content, the extracts presented a protective effect in A. cepa cells against the clastogenicity of MMS.
Keywords: chromosomal aberration; micronucleus; anticlastogenicity; protective effects; flavonoids